PENTINGNYA KOMPETENSI PEJABAT PEMBUAT KOMITMEN PENGADAAN BARANG/JASA PEMERINTAH DI KABUPATEN KEPULAUAN TALAUD DALAM MELAKSANAKAN TUGAS POKOK DAN KEWENANGANNYA SESUAI PERPRES NOMOR 54 TAHUN 2010 - Koropit, Fiktor Junaidi; Karamoy, Herman; Manossoh, Hendrik (Universitas Sam Ratulangi, 2016)
The purpose of this research was to analyze the implementation of the principle of the public procurement towards of the basic tasks and authority of Pejabat Pembuat Komitmen (PPK), PPK suitability educational qualifications and experience according to Presidential Decree No. 54 of 2010, as well as the PPK duty of public procurement that only an additional task in the middle of the duties and responsibilities in their SKPD. Informants in this study is the PPK in Talaud Islands Regency. Data were collected from interviews with informants and analyzed by qualitative approach. The results of this study indicate that the PPK in the Talaud Islands Regency are not yet fully implementing the principles of public procurement to perform basic tasks and authorities, the principles of procurement that can not be implemented properly is the principle of effective, due to the frequency found a discrepancy technical specifications result of procurement planning in construction work. Non-compliance with the technical specifications of procurement planning results caused by negligence of the provider and PPK is less thorough in explaining the details of the job. Appointment PPK in the Talaud Islands Regency in accordance with the qualifications required in the public procurement, as well as the PPK can perform basic tasks and additional tasks well. Keywords : PPK, Principle Of Public Procurement, educational and experience qualifications, additional tasks.